2009
DOI: 10.2337/dc08-0727
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Control of Diabetes and Impaired Fasting Glucose in New York City

Abstract: We used an interview to determine previously diagnosed diabetes and measured fasting plasma glucose to determine undiagnosed diabetes and IFG in a probability sample of 1,336 New York City adults. We assessed glycemic control and other clinical indicators using standardized NHANES protocols.RESULTS -The prevalence of diabetes among New York City adults was 12.5% (95% CI 10.3-15.1): 8.7% diagnosed and 3.8% undiagnosed. Nearly one-fourth (23.5%) of adults had IFG. Asians had the highest prevalence of impaired gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 18 publications
4
51
2
Order By: Relevance
“…20 Additionally, previous studies have identified that South Asians have an increased prevalence of diabetes, increasing the risk of cardiovascular disease. 21 The lower average education level of these groups suggests greater focus must be placed on the creation of culturally sensative, low literacy educational approaches to improve HTN and cardiovascular diesease awareness. The overall prevalence of HTN among NYC adults was 25.5%, which is lower than the national average (29.1%).…”
Section: Discussionmentioning
confidence: 99%
“…20 Additionally, previous studies have identified that South Asians have an increased prevalence of diabetes, increasing the risk of cardiovascular disease. 21 The lower average education level of these groups suggests greater focus must be placed on the creation of culturally sensative, low literacy educational approaches to improve HTN and cardiovascular diesease awareness. The overall prevalence of HTN among NYC adults was 25.5%, which is lower than the national average (29.1%).…”
Section: Discussionmentioning
confidence: 99%
“…In California, South Asian men ages 25-44 years have three times the relative risk of death from CVD in comparison to the age-matched general population [4]. Epidemiologic studies have documented that South Asian immigrants have higher prevalence of medical CVD risk factors than the general population, such as diabetes, dyslipidemia, and metabolic syndrome, possibly due to a genetic predisposition to insulin resistance and central adiposity [6,9,11,[22][23][24][25][26][27][28][29]. They also have high rates of behavioral CVD risk factors, including physical inactivity and diets low in fruits and vegetables [9, 23-25, 28, 30, 31].…”
Section: Introductionmentioning
confidence: 99%
“…Thorpe et al [18] reported fi ndings from the 2004 NYC HANES. New York City residents 20 years of age or older were evaluated via survey questions derived from physical examination, clinical and laboratory tests, face-to-face computer-assisted personal interviews, and audio computer-assisted self-interviews.…”
Section: Prevalence and Progression Of Diabetesmentioning
confidence: 97%